Evaluation of antimicrobial potential of partially purified proteins/peptide of Yellow Scorpion Buthus sindicus against Carbapenem-Resistant Acinetobactor baumannii and Pseudomonas aeruginosa. - Urooj, Sehrish; Amin, Rafat; Haque, Zeba (International Journal of Endorsing Health Science Research, 2021)
Background: Increasing antimicrobial resistance of microbes is one of the leading challenges faced by the medical community and human health. This study focused on a local scorpion species (Buthus sindicus) of Pakistan known for its potent antibiotic properties against Carbapenem-resistant Acinetobacter baumannii and Pseudomonas aeruginosa. Methodology: Venom extracted from Buthus sindicus tested against Carbapenem-resistant A. baumannii and P. aeruginosa in both crude and partially purified forms. The antibacterial Screening was performed by the Agar-disc diffusion method, using different concentrations of venom while using commercially available antibiotics as positive controls. Results: Among both two species P. aeruginosa and A. baumannii, were tested, there is no zone of inhibition found in any form of Buthus sindicus in the Disc Diffusion Method. Scorpion venom was processed with deionized water, PBS, and Tris-HCl and observed no difference in antibacterial activity. Conclusion: Our study concluded that no antimicrobial activity was found against any selected drug-resistant pathogens in the venom of Buthus sindicus, probably because of the lack of disulphide bonds.